Can a values and video-based activity increase knowledge or pro-environmental attitudes and behaviour? - Christodoulou Vasiliki; Bächtold Manuel; Iordanou Kalypso (E3S Web of Conferences)
Environmental education is important in the face of the climate crisis. Although previous studies suggest that knowledge could boost pro-environmental attitudes, behavioural change is complex and may go beyond knowledge acquisition. Previous research highlighted biospheric and altruistic values as motivational factors related to pro- environmental behaviour (PEB). Video-based education has arisen as an accessible environmental learning medium. Video-sharing platforms offer accurate educational videos, although, it is unclear if they can increase knowledge, PEB or change attitudes. An online experiment randomly allocated 72 students in two conditions to watch an informational video on climate change, with one condition engaging in a values clarification task. Participants completed questionnaires on environmental attitudes, PEB, environmental self-efficacy and knowledge. Cross-correlations indicated complex inter-relationships and a non-significant relationship between knowledge and PEB at baseline. The values clarification task did not offer an advantage on PEB or pro-environmental attitudes. Both conditions experienced increases in knowledge, indicating that watching an educational video on climate change contributes to knowledge acquisition. The findings highlight complex mechanisms involved in increasing pro-environmental attitudes and behaviours. The study was part of the project “Be the Change: Innovative Higher Education for Environmental Sustainability,” co-funded by the ERASMUS+ Programme of the European Union (Project number: 2022-1-SE01- KA220-HED-000087275).